Molecular subtypes of breast carcinoma and their association with clinicopathological parameters - Khaliq, Erum; Shawana, Summayya (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the frequency of molecular subtypes of breast carcinoma, and to determine their association with clinicopathological parameters. Method: The bi-directional, cross-sectional, analytical study was conducted from December 2022 to June 2023 at the Histopathology Department of Pakistan Naval Station Shifa Hospital, Karachi, and comprised 218 females aged 24-81 years with primary breast adenocarcinoma, including both prospective and retrospective cases. Immunohistochemistry was performed to categorise molecular subtypes. Allred scoring system was used to score oestrogen and progesterone receptors and human epidermal growth factor receptor-2. The cut-off value for proliferation index was set at 14%. Data was analysed using SPSS 27. Results: Among the 218 females with mean age 49.15+-12.83 years, Luminal B was the most frequently observed molecular subtype with 95(42.2%) cases, followed by Luminal A 49(23.4%), triple-negative breast cancer 41(18.8%) and human epidermal growth factor receptor 2 positive 33(15.6%) cases. A significant association of molecular subtypes was identified with grade and Ki67 (p<0.05). A high proliferation index was observed in all breast cancer molecular subtypes except Luminal A. Stage III presentation was most common among Luminal A 12(50%) and HER2-positive 10(66.7%) cases, whereas the majority of Luminal B 22(57.9%) and triple-negative breast cancer 10(52.6%) cases presented at stage II. Among all molecular subtypes, Luminal B exhibited the highest frequency of lymphovascular invasion 20(48.8%) and lymph node metastases 23(60.5%) cases. Among the six cases exhibiting perineural invasion, five were identified as Luminal B molecular subtype. Conclusion: Luminal B was found to be the predominant molecular subtype. Molecular subtype had a significant association with grade and proliferation index. Key Words: Breast cancer, Molecular subtypes, Immunohistochemistry, Ki67, Lymph node metastases, Tumour infiltrating lymphocytes.